Process optimization for the production of cheese- potato foods - Bisht, Anuragpal Singh (Indian Journal of Dairy Science, 2016)
Cheese is rich in fat and digestible protein but a poor source of carbohydrate; hence it was enriched with potato starch. A good quality of cheese-potato dip with adequate shelf life at room temperature of storage could be prepared by blending processed cheese and potato (in 1:1 ratio), cream, water and salt in mixer grinder. The product was optimized with respect to two types of cheese (processed and cheddar); three ratios (1:1, 1:2 &1:3) of cheese to potato; three levels of moisture content (70, 75 & 80%) and three heat treatments (10 psi/15 min, 15psi/5 min &15psi/10 min) of the product. Optimized product was autoclaved or retort processed for achieving higher shelf life. The composition of the product was fat -11.0%, protein – 6.32%, moisture – 76.1%, carbohydrate – 3.71% and ash – 2.02%.